CHALLENGES OF MODERN PALLIATIVE CARE. A NARRATIVE REVIEW - Justyna Berent; Paulina Rzepa; Łukasz Brzost; Marta Danuta Cendrowska; Beata Choromańska; Julia Maszewska; Szymon Milnerowicz; Julia Procyk; Barbara Ponitka; Karolina Stępień; Aleksandra Klukowska; Wiktoria Szumlińska; et al. (International Journal of Innovative Technologies in Social Science, 2025)
Palliative Care (PC) is a person-centered, integrated health service designed to support patients with serious illnesses in living actively and with minimal pain until death. It addresses the diverse needs of patients with both cancer and non-cancer diagnoses, aiming to improve quality of life (QoL), relieve symptoms, and provide comprehensive support to patients and their families. Despite its well-documented benefits and recommendations for early improvement, contemporary palliative care faces numerous challenges that limit its effectiveness and accessibility. This article explores the multifaceted obstacles confronting modern palliative care, analyzing why current practices often fall short of meeting patient needs and proposing areas for improvement to ensure timely, equitable, and effective palliative care delivery worldwide. Methods: The research methodology included an in-depth review if scientific articles available through databases such as Pubmed and Google Scholar. The team analyzed content from 2000 to 2025, placing special emphasis on the latest development. Through careful organization and validation, 83 of the most reliable publications were selected as the primary foundation for the study. The cited references of these publications were included in the analysis. Results: The scientific studies in this work have demonstrated that palliative care faces major challenges including limited global availability, insufficient specialized workforce, restrictive and inconsistent eligibility criteria, and stigma associated with its terminology. The growing demand from aging populations and increasing cancer cases further strains resources, while financial burdens and a fragmented, under-regulated mobile app market limit effective symptom management and care delivery. Additionally, delayed access to palliative care, insufficient integration within health systems, ethical and legal complexities, and inadequate psychological support for patients and families contribute to these challenges. Emerging technologies like AI offer promise but require careful implementation to maintain person-centered care and address ethical concerns. Conclusions: A well-functioning palliative care system is vital as it enables patients with serious illnesses to live actively and with improved quality of life, reduces symptom burden, and supports both patients and caregivers throughout the illness trajectory. Effective palliative care also has the potential to decrease healthcare costs by reducing unnecessary hospital admissions and facilitating care in preferred settings. Priorities for advancing palliative care include expanding service availability, revising eligibility criteria to focus on patient needs rather than prognosis, and improving education to reduce misconceptions and stigma. Sustainable funding, policy standardization, and multi-sector collaboration among healthcare providers, policymakers, patients, and communities are essential to building robust palliative care frameworks. Moreover, regulating and enhancing the accessibility of palliative care mobile applications can further support patients and caregivers by improving communication, symptom management, and advance care planning. Coordinated efforts across all stakeholders are crucial to overcoming existing challenges and ensuring equitable, high-quality palliative care that improves quality of life on a global scale.